Swage and hydraulic autofrettage impact on fracture endurance and fatigue life of an internally cracked smooth gun barrel Part II – The combined effect of pressure and overstraining. (September 2017) - Perl, M.; Saley, T.
Highlights: The combined 3-D SIFs for a single inner radial crack in a modern gun barrel. Novel realistic autofrettage stress fields, incorporating the Bauschinger effect. The influence of the type and level of autofrettage on the barrel's fatigue life. The beneficial effect of type and level of autofrettage on barrel's fatigue life. Abstract: The distributions of KIA (the stress intensity factor (SIF) due to autofrettage) along the front of a single inner radial semi-elliptical crack emanating from the bore of an autofrettaged smooth gun barrel were calculated for a large number of crack configurations in Part I of this paper. In order to assess the combined effect of overstraining and pressurizing the barrel, values of KIP, the SIF caused by internal pressure, and those of KIN, the combined SIF, are evaluated. The 3-D analysis is performed using the finite element (FE) method employing singular elements along the crack front. The novel realistic overstrain residual stress fields, incorporating the Bauschinger effect, for the two types of autofrettage presented in Perl and Saley (2016) are applied to the barrel. Hill's (Hill, 1950) residual stress field (RSF) is also applied for comparison reasons. The RSFs for Swage and Hydraulic autofrettage as well as Hill's solution are simulated in the FE analysis using equivalent temperature fields. Values of KIP and KIN = KIP + KIA are evaluated for a typical barrel of radii ratio R0 /Ri = 2, a wide range of crack depth to wall-thickness ratios ( a/t = 0.005–0.1), various crack ellipticities ( a/c = 0.2–1.0), and five levels of Swage, Hydraulic and Hill's autofrettage ( ε = 40%, 60%, 70%, 80%, and 100%). In total, 375 different 3-D cases are analyzed. A detailed study of the influence of the above parameters on the prevailing SIF is conducted. The results clearly indicate the favorable effect of all three types of autofrettage in enhancing the fatigue life of the barrel. However, the magnitude of such life extension depends on the type of autofrettage employed. Among the two realistic overstrain processes, Swage autofrettage is found to be considerably superior to Hydraulic autofrettage in prolonging the barrel's fatigue life. Hill's autofrettage is far from being realistic, overestimating the magnitude of the RSF, and, thus, exaggerating the barrel's fatigue life. Finally, the results highlight the importance of properly accounting for the Bauschinger effect including re-yielding, as well as the significance of the three dimensional analysis herein performed.